A comparison of social, family and inter-personal experiences of primary and secondary school children in Malaysia - Teoh, Hsien-Jin * (Sunway University College, 2004)
In this study, 307 primary and secondary school children were surveyed to ascertain the differences in their interpersonal experiences that may vary according to their ages. Group comparison analyses of the data indicated that comparatively the secondary school children used more coping strategies such as avoidance, distraction, emotion orientation and task orientation. The secondary school children also reported that their parents used less harsh discipline on them, and that they received less social support from their parents and teachers.